Feeding the Hungry Other: Levinas, Breastfeeding, and the Politics of Hunger. (2016) - Lee, Robyn
Abstract : Breastfeeding has become a subject of moral concern as its benefits have become well known. Encouraging mothers to breastfeed has been the goal of extensive public health promotion efforts. Emmanuel Levinas makes absolute responsibility to the Other central to his ethics, with giving food to the Other the paradigmatic ethical act. However, Levinas also provides an important critique of the autonomous individual who is taken for granted by breastfeeding promotion efforts. I argue that the ethical obligation to feed the hungry child must be recognized as coextensive with meeting the needs of women, especially given the current absence of important social and economic supports for breastfeeding. Under a Levinasian framework, each of us is ethically responsible for feeding children; this responsibility is not limited to mothers. This ethical responsibility needs to be expressed through improving social and economic supports necessary for those individuals who wish to breastfeed, instead of attempting to convince women to breastfeed. This ethical responsibility must also be understood in a broader context of a politics of hunger, which provides access to quality food for all, and goes beyond mere nutrition to include the importance of culture, touch, and intimacy in the enjoyment of food—what Levinas calls "good soup."